Notes on a universe in which we are only visitors - del Mundo, Ida Anita Quito (Animo Repository, 2012)
Notes on a Universe in Which We are Only Visitors is a creative writing thesis that explores different aspects of travel and place through literary poetry, short fiction, essays, a screenplay, visual art, and music. The collection maps a persons journey through the world and the ultimate search for an origin.